ISLAM IN CYPRUS: Navigating the Complexities of Ottoman-Era Traditions and Global Islamic Influences within a Transnational Context - Damayanti, Rizki (Journal of Contemporary Islam and Muslim Societies, 2024)
This study explores the complexities of Islam in Cyprus, focusing on the interplay between local and transnational Islamic identities within modern Muslim societies. Utilizing a qualitative case study approach, the research draws on secondary data from academic sources to analyze how these identities influence religious practices among Muslim communities in Cyprus. The thematic analysis reveals significant patterns in the historical evolution of Islam on the island, highlighting the diversity within its Muslim population and the impact of both textual and contextual factors on their practices. Findings indicate a dynamic interaction between local traditions, particularly Ottoman customs, and global Islamic influences, including transnational movements. This synthesis results in a unique Islamic identity that integrates historical continuity with contemporary adaptations. The insights gained contribute to a deeper understanding of how Muslim societies navigate their religious practices amidst local and global contexts, thereby enriching contemporary Islamic studies and discussions on religious integration in secular states.Keywords: Islam in Cyprus, modern Muslim societies, transnational context, Islamic identity, religious integration